Revelación de información sobre clientes, comunidad, empleados y medio ambiente en las entidades financieras espa\~nolas a través de las memorias de responsabilidad social corporativa (2007-2010) - Pablo Rodríguez Gutiérrez; Fernando José Fuentes García; Sandra María Sánchez-Ca\~nizares (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– The aim of this paper is to analyze the phenomenon of corporate social responsibility (CSR) in the Spanish banking sector through social responsibility reports. Based on the theories of legitimacy and Stakeholders justified the use of CSR to analyze the behavior information about its environment. As survey methodology used content analysis, in particular are analyzed and compared the information practices in relation to four pillars on which the RSC is organized: customers, community, employees and the environment. In particular, it proposes a content index of liability (IDR) that measures the quality and detail of information provided. The study concludes that the community and environment categories are the most generally reported, although nature are social institutions (savings banks and credit unions) more transparent about customers and community is concerned, on the evolution during the recent years have seen that the transparency of information does not increase, but remains stable or even decreased as in the case of the contents on customers, in addition, we find that the contents are related to the internal activity of the company remains concerned about the most institutions to address the impacts of their activities as financial intermediaries.
Keywords: M14; 330; Content analysis; Financial institutions; Global reporting initiative; Corporate social responsibility